A case of recurrent recurrent laryngeal nerve palsy: Ortner's Syndrome in pregnancy. Issue 1 (22nd April 2014) - Birts, William; Andrews, Sam; Thorning, Geoff
Summary: We report a case of a parturient with previously undiagnosed mitral stenosis who became symptomatic during two successive pregnancies from the rare condition, Ortner's syndrome. The diagnosis was only made shortly after delivery of her second child. This report describes her unusual presentation, subsequent diagnosis and management. On review of the literature, we believe this is the first description of Ortner's syndrome diagnosed in the obstetric setting. We discuss causes of Ortner's syndrome and the difficulties of undiagnosed cardiovascular pathology in the obstetric patient.